Varying Immunizations With Plasmodium Radiation-Attenuated Sporozoites Alter Tissue-Specific CD8+ T Cell Dynamics - Frank, Roland; Gabel, Michael; Heiss, Kirsten; Mueller, Ann-Kristin; Graw, Frederik (Frontiers in Immunology, 2018)
Whole sporozoite vaccines (WSV) represent one of the most promising strategies to induce protection against malaria. However, the development of efficient vaccination protocols still remains a major challenge. To understand how the generation of immunity is affected by variations in vaccination dosage and frequency, we systematically analyzed intrasplenic and intrahepatic CD8+ T cell responses following varied immunizations of mice with radiation-attenuated sporozoites (RAS). By combining experimental data and mathematical modeling, our analysis indicates a reversing role of spleen and liver in the generation of protective liver-resident CD8+ T cells during priming and booster injections: While the spleen acts as a critical source compartment during priming, the increase in vaccine-induced hepatic T cell levels is likely due to local reactivation in the liver in response to subsequent booster injections. Higher dosing accelerates the efficient generation of liver-resident CD8+ T cells by especially affecting their local reactivation. In addition, we determine the differentiation and migration pathway from splenic precursors towards hepatic memory cells thereby presenting a mechanistic framework for the impact of various vaccination protocols on these dynamics. Thus, our work provides important insights into organ-specific CD8+ T cell dynamics and their role and interplay in the formation of protective immunity against malaria.